Transnacionalsm and territoriality in southh- south agrarian movements - Milhorance, Carolina (2018)
Based on an analysis of the transnational networks of South-South activism, this article discusses how the opposition to the expansion of Brazilian agribusiness takes different forms in the territories in which it is located. The campaign against the Triangular Cooperation Program for Agricultural Development of the Tropical Savannas in Mozambique (ProSavana) is taken as a case study to examine and qualify both symbolic and material aspects related to transnational activism. It is argued that the mobilization contrary to the program occurred, to a great extent, in a decoupled way from the political-economic contexts of the affected territories.